Allopatric speciation, niche conservatism and gradual phenotypic change in the evolution of European green lizards. (18th October 2022) - Enriquez‐Urzelai, Urtzi; Martínez‐Freiría, Fernando; Freitas, Inês; Perera, Ana; Martínez‐Solano, Íñigo; Salvi, Daniele; Velo‐Antón, Guillermo; Kaliontzopoulou, Antigoni
Abstract: Aim: The contributions of historical biogeography, morphology and climatic niche evolution in shaping species diversification have been typically examined separately. To fill this gap, we assessed the relative role of geologic history, environment and phenotypic trait evolution in lineage diversification of green lizards in the Mediterranean biodiversity hotspot. Location: Eurasia and North Africa. Taxon: Green lizards (genera Timon and Lacerta ). Methods: For all green lizard lineages, we characterized distributional ranges and external morphological traits across discrete biogeographical areas, occupied macro‐habitats and climatic niches using environmental variables that represent average and extreme climatic conditions. To assess the contribution of geographical factors in shaping diversity patterns, we evaluated the fit of 24 biogeographical models. We used BAMM and estimated phylogenetic signal to assess the rates of lineage diversification and of phenotypic and climatic niche evolution, and to determine whether these processes occurred steadily or at specific time periods as a response to palaeogeological or palaeoclimatic events. Finally, we tested for associations between phenotypic traits and lineage diversification using trait‐dependent diversification analyses (QuaSSE, ES‐sim and STRAPP). Results: Biogeographical analyses favoured a dispersal–vicariance model explaining speciation patterns in green lizards, including jump dispersal and constrained dispersal by geographical distance. Lineages accumulated gradually towards the present, with minor divergence in morphological traits and conservatism of climatic niches. In contrast, in the Lacerta agilis lineage, niche evolution may have allowed expansion towards colder environments. Morphological and climatic niche evolution were uncoupled from diversification rates. Main Conclusions: Biogeographical processes largely explain the constant lineage diversification of green lizards in the Mediterranean Basin since the Miocene, followed by gradual phenotypic divergence unrelated to cladogenesis. Climatic niche conservatism promoted the accumulation of lineages within the Mediterranean, except for L. agilis, where climatic niche evolution might underpin its range spread towards higher latitudes.